One hundred years after the expedition by Harvard University to Peru to investigate Carrion’s disease. Lessons for science (2016)
In 1913, around 100 years ago, the Harvard University sent an expedition to Peru, led by Richard Strong, to investigate Carrion’s disease. This paper provides a critical review of the scientific research carried out in this expedition.Richard Strong was a physician who performed unethical human experimentation in the Philippines and China. In Peru, Strong conducted experiments on humans to inoculate wart secretions to a psychiatric patient, which led him to replicate the Peruvian wart in this individual, although he could not replicate Oroya fever. Based on this experiment, and without taking into account epidemiological and clinical evidence, the Harvard expedition erroneously concluded that Oroya fever and Peruvian wart were two different diseases.A retrospective review of the scientific work conducted by the expedition in Peru allows drawing the following lessons for science: a) disapproving unethical human experimentation conducted by the expedition; b) to determine the cause of infectious diseases, it is necessary to obtain the best scientific, experimental and observational evidence, and c) to acknowledge that, despite the poor infrastructure, researchers in developing countries are able to produce high-quality scientific knowledge that may surpass the knowledge generated by researchers in developed countries.